Health-related quality of life of patients 12 months following surgical intensive care discharge - F. Karachi; S. Hanekom; M. Faure (AOSIS, 2011)
Health  related  quality  of  life  (HRQoL)  and  the  effect  of  selected  socio-demographic  and  clinical  intensive  care  variables  on  HRQoL of  patients  12  months  following  adult  surgical  intensive  care  unit  discharge in  the  Western  Cape  was  evaluated.  A  prospective  observational  study  was conducted.  The  sample  comprised  46  patients  who  had  survived  12  months following discharge. Structured telephonic interviews were conducted using a self-developed  and  SF-36v2  HRQoL  questionnaire.  Data  was  analyzed  using Stastica 7 and values were accepted as significant at the 5% level. Low mean HRQoL  domain  scores  (43%  -  53%)  were  found  implying  a  poor  HRQoL outcome. Physical functioning [43.5%], Role Play [44.5%] and Role Emotion [43.1%] scores were specifically lower than the other HRQoL domain scores. Age and severity of illness scores (APACHE II) were significantly associated with the social functioning (p=0.01) and physical functioning (p=0.02) scores  respectively. APACHE  II  may  be  a  useful  contributor  in  predicting  long-term  physical  functioning  outcomes  in  patients  following  surgical  ICU  discharge.  The  HRQoL  outcomes  are  slightly  lower  than  that  found  for  inter-national ICU populations however responses in the domains affected are comparable. Low physical functioning, role play  and  role  emotion  scores  indicate  a  need  for  further  physical  and  emotional  rehabilitation  following  surgical  ICU discharge.